KEPASTIAN HUKUM ATAS PENGALOKASIAN PERUNTUKAN LAHAN PADA KAWASAN HUTAN DI ATAS HAK PENGELOLAAN OTORITA BATAM - WAHYUDI PUTRA WINATA (PREMISE LAW JURNAL, 2015)
The overlapping of land allocation in Batam authority area began with the issuance of the Decree of the Minister of Forestry No. 173/Kpts-II/1986 on the Allocation of Forest Area in Riau Province (TGHK). The Minister of Forestry then followed up with the Decree of the Minister of Forestry No. 47/Kpts-II/1987 on the Allocation of Forest Area in Batam Island. In reality, this decree has ignored the TGHK provision. The result of the research showed that legal certainty on the overlapping of land allocation in forest area on the land of Batam indicated that the Decree No.47/Kpts-II/1987 and its certified copy was had to be ignored; therefore, the ownership management rights of Batam Authority was in effect. The legal protection for land owners in Batam Authority area was concerned with the old rights owned by villagers by setting the location of old villages in Batam under the Regional Regulation (Perda) No. 2/2004 on RT/RW (neighborhood/citizen associations) of Batam in 2004-2014. The legal protection for the land rights which were obtained based on the distribution in parts of HPL land by Batam Authority to the third party was by providing alternative land from the outside forest area. In the case of the resolution for the overlapping of land allocation of Batam Authority Management Rights, the Authority Board of the Development of Batam Industrial Area, supported by Batam Municipality Administration in 2001, lodged a request for structuring forest area in Batam Island through mechanism of changing the of forest area allocation to the Minister of Forestry. Keywords: Legal Certainty, Management Rights, Batam Authority